2016
DOI: 10.1007/s00345-016-1964-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of surveillance versus adjuvant chemotherapy for patients with stage IA and IB nonseminomatous testicular germ cell tumors

Abstract: Our results indicate that adjuvant chemotherapy is associated with improved RFS compared with surveillance for CS I NSGCT patients. Moreover, the treatment strategy is an important prognostic indicator for RFS and a predictive factor for relapse. Although adjuvant chemotherapy seems to be a suitable treatment for patients with risk factors for relapse, surveillance is still preferred management option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Patient autonomy should be respected and in order to help the patients, it is necessary to give patients information on different short and long-term risks with adjuvant treatment versus full chemotherapy, in case of relapse. Treating in the adjuvant situation decreases the risk of relapse significantly [29,49] and hence reduces the risk of side-effects caused by multiple courses of chemotherapy needed in case of metastatic disease.…”
Section: Annals Of Oncologymentioning
confidence: 99%
“…Patient autonomy should be respected and in order to help the patients, it is necessary to give patients information on different short and long-term risks with adjuvant treatment versus full chemotherapy, in case of relapse. Treating in the adjuvant situation decreases the risk of relapse significantly [29,49] and hence reduces the risk of side-effects caused by multiple courses of chemotherapy needed in case of metastatic disease.…”
Section: Annals Of Oncologymentioning
confidence: 99%
“…Similarly, with regard to postoperative adjuvant therapy, it has been reported that recurrence of nonseminomatous testicular germ cell tumors of stage IA and IB is significantly reduced by performing adjuvant chemotherapy [17]. However, in this case, there is no clear evidence of the effectiveness of adjuvant therapy when gross curative resection is performed.…”
Section: Discussionmentioning
confidence: 89%
“…Post-surgical treatment was based on histopathologic features and disease stage at surgery (2,27,28). Management options after surgery included surveillance, adjuvant chemotherapy, radiotherapy and RPLND (2,30). Considering the relatively low risk of relapse in testicular cancer, many guidelines recommend surveillance as the preferred initial treatment for all stage I SGCT and low-risk stage I NSGCT (31).…”
Section: Discussionmentioning
confidence: 99%
“…Eventual relapses may be cured by radiation or chemotherapy (2). Adjuvant treatments have declined in recent decades, as surveillance has been increasingly used to avoid unnecessary treatment and related long-term toxicities (2,30). Indeed, historically active surveillance became an option in the 1980's when it was demonstrated that cisplatin-based chemotherapy could cure almost all recurrences.…”
Section: Discussionmentioning
confidence: 99%